A Balance-of-Payments-Constrained Growth Model for a Small Commodity Exporting Country: Argentina Between 1971 and 2016. Issue 4 (4th July 2022) - Massot, Juan Miguel; Merga, Román David
ABSTRACT: We study the balance of payments (BOP) as a constraint on economic growth, focusing on Argentina's economy between 1971 and 2016. The data show that Thirlwall's balance-of-payments-constrained growth model cannot explain Argentina's average growth during this period, which witnessed high growth in the terms of trade. We expand Thirlwall's model based on recent empirical indications that exporters set their prices in foreign currencies. Thus, we show new ways in which the terms of trade and real exchange rate impact the growth rate compatible with the BOP equilibrium. While prices affect the growth rate compatible with the BOP equilibrium mainly through changes in the original model's quantities, the proposed extension finds a stronger direct effect of the terms of trade. Through the extended model, we find that the weak and strong tests of Thirlwall's Law are not rejected. Further, we show the consistency of the results regardless of the assumed country size or presence of structural economic breaks. Consequently, we argue that prior literature was inconclusive for Argentina as it did not consider invoicing of international trade in foreign currency, thus disregarding the full effect of the terms of trade and real exchange rate on growth compatible with the BOP equilibrium.